Democracy and Crisis Challenges in Turbulent Times (Springer International Publishing, 2018)
In light of the public and scholarly debates on the challenges and problems of established democracies, such as a lack of participation, declining confidence in political elites, and the deteriorating capabilities of democratic institutions, this volume discusses the question whether democracy as such is in crisis. On the basis of the shared concept of embedded democracy, it develops a range of conceptual approaches to empirically analyzing the challenges of democracy and their potential transformation into crisis phenomena. The book is divided into three parts, the first of which highlights various aspects of political participation, such as political inequality in voting. In turn, Part II focuses on problems of political representation, while Part III assesses whether processes such as globalization, deregulation, and the withdrawal of the state from important policy areas have limited the political control and legitimacy of democratically elected governments. .